Primary cutaneous B-cell lymphomas. Clinical aspects and pathology - Fink-Puches, R. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Primary cutaneous B-cell lymphomas are defined as malignant B-cell proliferations presenting with cutaneous involvement alone and no evidence of extracutaneous manifestations when complete staging has been performed. The major subtypes are: cutaneous follicle center-cell lymphoma, cutaneous marginal zone B-cell lymphoma/immunocytoma, and large B-cell lymphoma of the leg. A correct diagnosis can be achieved only in the context of knowledge of the clinical findings. Progress in terms of classification and biology is associated with the application of modern techniques including immunohistologyand laser beam microdissection followed by molecular analysis. Future definitions of primary cutaneous B-cell lymphomas will be based on their molecular abnormalities and their etiology and pathogenesis. Awareness of the special clinical behavior of primary cutaneous B-cell lymphoma should prevent unnecessarily aggressive treatment. Primary cutaneous B-cell lymphomasoccur far more frequently than generally believed (1). Patients with cutaneous B-cell lymphomas can be divided into 2 groups: Primary cutaneous B-cell lymphomas are defined as presence of disease limited to the skin after complete staging procedures have been performed. Patients with secondary cutaneous B-cell lymphomas show extracutaneous disease and subsequent development of skin lesions. In recent years great attention has been accordedto the group of primary cutaneous B-cell lymphomas. The European Organization for Research and Treatment of Cancer (EORTC)-Cutaneous Lymphoma Project Group proposed a new classification for primary cutaneous lymphomas in1997 (2). The most common types of primary cutaneous B-cell lymphomas are cutaneous follicle center-cell lymphoma, cutaneous marginal zone B-cell lymphoma/immunocytoma, and large B-cell lymphoma of the leg.
Keywords: dermatologija; Diagnosis; diagnostika; Kožne novotvorbe; limfom; Limfom B-celični; Lymphoma, B-Cell; Pathology; Skin Neoplasms; Therapy; zdravljenje